2016
DOI: 10.1155/2016/6303490
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Experience Destiny? Review of Research on Long-Term Outcomes following International Adoption with Special Reference to the British Chinese Adoption Study

Abstract: The pathway from adverse early experience to adulthood for internationally adopted children is complex in identifying key influences, impacts, and outcomes. This review arose from the authors' involvement in the British Chinese Adoption Study, a recent outcomes study that explored the links between early orphanage care, adoptive experiences, and midadulthood. It differs from previous reviews in focusing on a greater length of time since adoption. Both quantitative and qualitative studies were included to allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This observation is consistent with other studies that found that people in adoption had two to three times more risk of total suicide than non-adopted people (33). This finding agrees with other systematic reviews or metaanalyses, which found poorer outcomes for adoptees than persons from the general population on indicators of intelligence quotient, cognitive functioning, social adjustment, school achievement, behavioral troubles, psychological problems, and psychiatric diagnoses (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This observation is consistent with other studies that found that people in adoption had two to three times more risk of total suicide than non-adopted people (33). This finding agrees with other systematic reviews or metaanalyses, which found poorer outcomes for adoptees than persons from the general population on indicators of intelligence quotient, cognitive functioning, social adjustment, school achievement, behavioral troubles, psychological problems, and psychiatric diagnoses (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Discussionsupporting
confidence: 92%
“…Some systematic reviews or meta-analyses have been carried out to summarize the association between the adoption situation and outcomes in intelligence quotient (9,10), cognitive functioning (12,13), social functioning (14), school performance (15,16), behavioral problems (14)(15)(16)(17), psychological adjustment (13)(14)(15)18), and mental health (14,15,(18)(19)(20)(21). However, no meta-analysis consolidates the information about the specific association between the adoption situation and suicide attempt.…”
mentioning
confidence: 99%
“…Six systematic reviews and meta-analyses of severe neglect and mental health were identified (Fensbo, 2004; Grant, Rushton, & Simmonds, 2016; Johnson et al, 2006; Juffer & van IJzendoorn, 2005, 2007; Latimer et al, 2012). Two of these also addressed outcomes in the areas of cognitive development and attachment (Fensbo, 2004; Johnson et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Among those studies that have extended to mid-life, most have examined psycho-social outcomes with little data on the intervening years, or have focused in depth on important but relatively narrow areas of adult experiences such as dealing with racism (Grant, Rushton and Simmonds, 2016). This leaves a gap in understanding the influence of other events in adult life.…”
Section: Introductionmentioning
confidence: 99%